Review Penerapan Pembangkitan Terdistribusi (DG) pada Sistem Tenaga Listrik - Leily Wustha Johar; Hendi Matalata (Universitas Batanghari Jambi, 2026)
Distributed generation (DG) has become an important solution in modern power systems to address increasing electricity demand, improve system efficiency, and support the integration of renewable energy sources. DG refers to small to medium scale power generation units connected directly to the distribution network or located near load centres. This paper discusses the application of distributed generation in distribution systems, focusing on technical aspects such as power loss reduction, voltage profile improvement, and protection coordination. A technical analysis is presented through power loss and voltage drop calculations on a 20 kV distribution feeder, demonstrating that proper placement of DG can significantly reduce feeder losses and enhance voltage performance. Further more, a single-line diagram of 150/20kV substation integrated with distributed generation is developed, including current transformers (CT), potential transformers (PT/CVT), circuit breakers, and protection schemes. Several case studies of DG implementation in Indonesia, such as roof top photovoltaic systems and micro-hydro power plants, a real so discussed. There sults indicatet hat distributed generation, when properly planned and coordinated, can improve system reliability, reduce technical losses, and support the transition toward sustainable and renewable-based power systems.